The implications of time on the ground on running economy: less is not always better; Journal of Experimental Biology; Vol. 222, No. 6 - Lussiana T. Thibault; Patoz A. Aurelien; Gindre C. Cyrille; Mourot L. Laurent; Kim H.-L. Hebert-Losier (2019, 2019)
Title screen